2021
DOI: 10.15252/emmm.202114563
|View full text |Cite
|
Sign up to set email alerts
|

A homozygous R148W mutation in Semaphorin 7A causes progressive familial intrahepatic cholestasis

Abstract: Semaphorin 7A (SEMA7A) is a membrane-bound protein that involves axon growth and other biological processes. SEMA7A mutations are associated with vertebral fracture and Kallmann syndrome. Here, we report a case with a mutation in SEMA7A that displays familial cholestasis. WGS reveals a SEMA7A R148W homozygous mutation in a female child with elevated levels of serum ALT, AST, and total bile acid (TBA) of unknown etiology. This patient also carried a SLC10A1 S267F allele, but Slc10a1 S267F homozygous mice exhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 43 publications
(67 reference statements)
1
14
0
Order By: Relevance
“…We noted that in some cases, SLC10A1 S267F homozygotes with a combination of other gene mutations or diseases showed different symptoms, such as jaundice and/or liver dysfunction, late fetal loss, or urticarial rashes (13,15,17,25,26). We confirmed that serum BA levels increased asymptotically in SLC10A1 S267F homozygotes.…”
Section: Relationship Of the Slc10a1 S267f Mutation And Other Gene Mu...supporting
confidence: 74%
See 1 more Smart Citation
“…We noted that in some cases, SLC10A1 S267F homozygotes with a combination of other gene mutations or diseases showed different symptoms, such as jaundice and/or liver dysfunction, late fetal loss, or urticarial rashes (13,15,17,25,26). We confirmed that serum BA levels increased asymptotically in SLC10A1 S267F homozygotes.…”
Section: Relationship Of the Slc10a1 S267f Mutation And Other Gene Mu...supporting
confidence: 74%
“…Some studies have mentioned that patients with SLC10A1 S267F display worse clinical phenotype (such as liver dysfunction), always accompanied by other damage variants. Also, our previous results indicated that Slc10a1 S267F homozygous mice displayed normal levels of serum BA and did not cause hypercholanemia (26). Thus, to our knowledge, there are probably other variants in SLC10A1 S267F homozygotes; in this regard, 5 candidate SNPs are described below.…”
Section: Discussionmentioning
confidence: 76%
“…Homozygous Sema7a R145W mutant mice (C57BL/6 J background) were designed and generated by Shanghai Model Organisms Center via the Cas9-targeted single guide RNA of 5′ ATGCCCGGAAGCCCAGCTGCTGG 3′. The generation protocol for Sema7a R145W mutant mice has been described previously [ 8 , 9 ]. Liver samples were collected from wild-type (n = 4) and Sema7a R145W homozygous mice (n = 5).…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidence has shown that the SEMA7A R148W mutation ( Sema7a R145W in mice) is a gain-of-function mutation and a risk factor involved in progressive familial intrahepatic cholestasis (PFIC) and non-alcoholic fatty liver disease (NAFLD). Pan et al demonstrated that the SEMA7A R148W mutation could disturb bile acid transport by reducing bile salt export pump and multidrug resistance-associated protein-2 expression, resulting in PFIC development [ 8 ]. Zhao et al reported that the mutation could promote hepatocyte lipid accumulation via integrin β1 and aggravate NAFLD progression [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…A recent study reported that a novel type of PFIC could be induced by a homozygous R148W mutation of the SEMA7A gene. 30 At present, there no curative drugs for FIC, but UDCA and bile acid blocking agents are generally recommended. A dietary supplement of medium-chain triglycerides and fat-soluble vitamins are also generally recommended.…”
Section: Ficmentioning
confidence: 99%